A Prospective Study of Injury Pattern in Victim of Assault Attended in South Mumbai Government Hospital - Thube, H R; Chikhalkar, B G; Nanandkar, S D (Journal of Indian Academy of Forensic Medicine, 2015)
Assault was the main crime since long back from history. The present study was conducted in accident and emergency Department of Grant Medical College and Sir JJ Hospital located in south Mumbai over the period of two years from October 2011 to September 2013. Total 1288 cases of assault observed out of which 1100 were male (85.4%) and 188 were female (14.6%). The age group which was maximally affected in case of male and female was same i.e. 21-30 year. In males majority of injuries were simple in nature 803 (73%). While in females no grievous injury noted. Most commonly body part involved in assault was head face and neck 959 (47.92%). The commonest injury in male victim was lacerations 543 (49.4%).The weapon of assault in male victims was hard and blunt object in maximum 51.4% while in females 45.2% were body parts such as fist and kicks. Out of 272 grievous injuries the 31.2% injuries were caused by hard and blunt weapons. Thorough examination and interpretation of injury is of vital medico-legal importance and plays crucial role for judiciary to deal with interpersonal violence.